CARCINOMA MAMÁRIO COM MÚLTIPLAS METÁSTASES EM CÃO: RELATO DE CASO - ANDRADE BAZZAN , THAINA; ANDRÉIA INKELMANN , MARIA; NASCIMENTO HÖRZ , SABRINA; ZANFRA SERENO , BEATRIZ; NUNES DOS SANTOS , ANDREI (Salão do Conhecimento, 2021)
Câncer/Tumor